The effects of dietary supplementation with inulin and inulin‐propionate ester on hepatic steatosis in adults with non‐alcoholic fatty liver disease. Issue 2 (16th September 2018) - Chambers, Edward S.; Byrne, Claire S.; Rugyendo, Annette; Morrison, Douglas J.; Preston, Tom; Tedford, Catriona; Bell, Jimmy D.; Thomas, Louise; Akbar, Arne N.; Riddell, Natalie E.; Sharma, Rohini; Thursz, Mark R.; et al.
Abstract : The short chain fatty acid (SCFA) propionate, produced through fermentation of dietary fibre by the gut microbiota, has been shown to alter hepatic metabolic processes that reduce lipid storage. We aimed to investigate the impact of raising colonic propionate production on hepatic steatosis in adults with non‐alcoholic fatty liver disease (NAFLD). Eighteen adults were randomized to receive 20 g/d of an inulin‐propionate ester (IPE), designed to deliver propionate to the colon, or an inulin control for 42 days in a parallel design. The change in intrahepatocellular lipid (IHCL) following the supplementation period was not different between the groups ( P = 0.082), however, IHCL significantly increased within the inulin‐control group (20.9% ± 2.9% to 26.8% ± 3.9%; P = 0.012; n = 9), which was not observed within the IPE group (22.6% ± 6.9% to 23.5% ± 6.8%; P = 0.635; n = 9). The predominant SCFA from colonic fermentation of inulin is acetate, which, in a background of NAFLD and a hepatic metabolic profile that promotes fat accretion, may provide surplus lipogenic substrate to the liver. The increased colonic delivery of propionate from IPE appears to attenuate this acetate‐mediated increase in IHCL.